Production and nutrition of 'Tahiti' lime as affected by nitrogen and potassium fertilization in five crop seasons - Silva, José Tadeu Alves da; Silva, Inêz Pereira da; Simão, Fúlvio Rodrigues (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to estimate nitrogen and potassium rates, in order to obtain maximum technical and economic efficiency and the critical levels of these two nutrients on leaves of irrigated 'Tahiti' lime tree, grown in a Typic Quartzipsamment soil in five crop seasons. A randomized complete block design was carried out with four replicates, in a 4x5 factorial arrangement, with four N rates (0, 25, 50, and 100 kg ha‑1) and five K2O rates (0, 25, 50, 100, and 200 kg ha‑1). The estimated rates to achieve the maximum technical efficiency were 90, 99, 69, 66, and 100 kg ha‑1 N, and for the maximum economic efficiency, 85, 95, 67, 64, and 93 kg ha‑1 N, for the first, second, third, fourth, and fifth crop seasons, respectively. The rates of K2O to obtain the maximum technical efficiency were 126, 116, 101, 98, and 95 kg ha‑1, and for maximum economic efficiency, 112, 105, 94, 90, and 88 kg ha‑1 K2O, respectively, for the first, second, third, fourth, and fifth crops. The average, estimated critical levels for leaf contents are 25 g kg ‑1 N and 22 g kg ‑1 K, in five crop seasons.